Storage of male Glossina palpalis gambiensis pupae at low temperature: effect on emergence, mating and survival - Mutika, Gratian N (BioMed Central, 2014)
BACKGROUND: Procurement of sterile tsetse flies (Glossina palpalis gambiensis) from Burkina Faso for an eradication programme in Senegal that incorporates the sterile insect technique (SIT) required the development of transport and handling protocols that would allow retaining the female flies in the rearing facility and transport of the male flies as irradiated pupae. The proposed handling scheme included the chilling of the male pupae after the female emergence and transport to Senegal under low temperatures. The effect of exposing male pupae of G. p. gambiensis to low temperature immediately prior to emergence was investigated. METHODS: The parameters of interest were emergence rate, insemination potential, survival of adult male, male ability to participate in mating activities and productivity of females mated with these males. Production was assessed in laboratory rearing cages and mating behaviour in field cages. Male flies that emerged after the female emergence flush from pupae stored at 10°C or 12.5°C for 5 or 7 days were used in the investigations with flies that emerged under standard colony conditions as control. Males that were 3, 6 or 9 days old competed for mating opportunities with 3 day old females. RESULTS: The emergence of males after storage of pupae at low temperature (10°C and 12.5°C) for 3, 5, or 7 days was similar to those kept under standard colony conditions while emergence of flies stored at 15°C started before the storage period was over. Survival of males that emerged from pupae stored at low temperature for varying periods was more than 60% at 30 days post emergence (control more than 75%). The fecundity of females inseminated by males that emerged from pupae stored at low temperature for varying periods ranged from 0.33±0.16 to 0.73±0.04 pupae per female per 10 days (control 0.60±0.16). The older males, irrespective of treatment, out-competed the younger males and 3 day- old males transferred lower amounts of seminal contents to the females. CONCLUSIONS: Storage of male pupae at low temperature for periods up to 7 days at the end of the male pupal period could not be directly associated with impairment of mating activity.